Synergistic Effects of Silicon and Ferrous Sulfate on Reducing Arsenic and Cadmium Accumulation in Rice from Co-Contaminated Soil - Yanlin You; Xiaodong Guo; Jianyu Chen; Zhiqin Liu; Qiuying Cai; Jinyong Yu; Wanli Zhu; Yuna Wang; Hanyue Chen; Bo Xu; Yanhui Chen; Guo Wang (Agronomy)
The co-contamination of arsenic (As) and cadmium (Cd) in paddy soils threatens rice safety, yet synergistic mitigation strategies using silicon (Si) and ferrous sulfate (FeSO4) remain underexplored. This study integrated hydroponic and soil pot experiments to evaluate Si-FeSO4 interactions on As/Cd accumulation and rice growth. Hydroponic trials employed 21-day-old rice seedlings exposed to 0.5 mg As(III)/Cd(II) L−1 with/without 70 mg Si L−1 and 30–70 mg Fe L−1, followed by sequential harvesting at 14 and 21 days. Soil experiments utilized co-contaminated paddy soil (50 mg As kg−1 and 1.2 mg Cd kg−1) amended with Si (80 or 400 mg kg−1) and Fe (100 or 1000 mg kg−1), with pore water dynamics monitored over 120 days. Hydroponic results demonstrated that 70 mg Si L−1 combined with 30 or 70 mg Fe L−1 enhanced shoot biomass by 12–79% under As stress, while simultaneously reducing shoot As concentrations by 76–87% and Cd concentrations by 14–33%. Iron plaque induced by FeSO4 exhibited contrasting adsorption behaviors: hydroponic roots immobilized both As and Cd (p < 0.01), whereas roots in soil primarily retained Cd (p < 0.05). In soil experiments, the optimal treatment of 100 mg Fe kg−1 and 400 mg Si kg−1 (Fe1 + Si2) increased grain biomass by 54%, while reducing As and Cd concentrations by 37% and 42%, respectively. However, a higher Fe dosage (Fe2: 1000 mg kg−1 Fe) paradoxically increased grain Cd concentrations. Mechanistically, Si amendment elevated soil pH (Δ + 0.72), facilitating Cd immobilization, while FeSO4 lowered pH (Δ−0.07–0.53), increasing Cd mobility. A strong correlation between soluble Cd and plant uptake was observed (p < 0.01), while changes in As accumulation were unrelated to aqueous behavior. The optimized Si/Fe molar ratio of 7.95:1 effectively mitigated As and Cd co-accumulation, offering a dual-functional strategy for safe rice cultivation in contaminated soils.